A permanência na universidade de estudantes oriundos das ações afirmativas: uma revisão de escopo - Medeiros, Bianca Casseb (Universidade Federal de São Carlos, 2020)
Affirmative Actions (AA) are special and temporary measures that seek to remediate a discriminatory past. They aim to accelerate the fight against inequalities faced by socially vulnerable groups, such as ethnic and racialized groups. At the academy level, AA have been implemented through strategic policies, practices and social resources that provide access and permanence for groups historically excluded in these spaces, in order to promote social change within the principles of equality. With the diversity that exists and the inequalities that still remain, it is necessary that universities are prepared to deal with the new challenges. This study investigates how Brazilian literature has approached the permanence processes of students who entered Brazilian universities through AA policies, taking as basis for reflection, the students' own narratives. Based on the theoretical framework of occupational justice (OJ), a scope review was carried out following the parameters proposed by Arksey and O'Malley, studies published in the last five years, on the subject were examined. The review aimed to reflect on the Brazilian social contemporary experience, after the consolidation of Federal Law no. 12,711 / 2012 (Quota Law), which through its execution destinates 50% of the vacancies in undergraduate courses to self-declared afro descendants, mixed race, indigenous people, people with disabilities and students who attended high school entirely in publicly funded schools. From a thematic analysis of the data, it was possible to understand the challenges, strengths and meanings of staying in the academy, revealing the ways in which the occupational possibilities of this audience are built in the university context.
Affirmative action and student's permanence at university: a scoping review
Keywords: Ações afirmativas; Ensino superior; Permanência; Justiça ocupacional; Terapia ocupacional; Affirmative actions; University education; Permanence; Occupational justice; Occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL